2021
DOI: 10.1101/2021.04.23.441102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amino acid residues involved in inhibition of host gene expression by influenza A/Brevig Mission/1/1918 PA-X

Abstract: Influenza A virus (IAV) PA-X protein is a virulence factor that selectively degrades host mRNAs leading to protein shutoff. This function modulates host inflammation, antiviral responses, cell apoptosis, and pathogenesis. In this work we describe a novel approach based on the use of bacteria and a plasmid encoding the PA-X gene under the control of the bacteriophage T7 promoter to identify amino acid residues important for A/Brevig Mission/1/1918 H1N1 PA-X’s shutoff activity. Using this system, we have identif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…IAV NS1 modulates the inhibition of IFN production through variable interventions (Baker et al, 2015;Cheng et al, 2015;Nogales et al, 2017a;Nogales et al, 2017b;Nogales et al, 2017c;Hilimire et al, 2020;Martinez-Sobrido et al, 2020;Chiem et al, 2022;Nogales et al, 2022). However, other IAV proteins, including PA-X (Chiem et al, 2021), PB1-F2 (Varga and Palese, 2011;Varga et al, 2012), or PB2 have also been shown to be involved in inhibition of host antiviral responses during IAV infection (Forero et al, 2015;Yang et al, 2022). Following IAV infection, two major cellular pathways are activated to initiate the antiviral innate immune response: Toll-like receptors (TLRs) and RIG-I-like receptors (RLRs) (Iwasaki and Pillai, 2014) (Figure 5).…”
Section: Iav Ns1 Inhibition Of Ifn Productionmentioning
confidence: 99%
“…IAV NS1 modulates the inhibition of IFN production through variable interventions (Baker et al, 2015;Cheng et al, 2015;Nogales et al, 2017a;Nogales et al, 2017b;Nogales et al, 2017c;Hilimire et al, 2020;Martinez-Sobrido et al, 2020;Chiem et al, 2022;Nogales et al, 2022). However, other IAV proteins, including PA-X (Chiem et al, 2021), PB1-F2 (Varga and Palese, 2011;Varga et al, 2012), or PB2 have also been shown to be involved in inhibition of host antiviral responses during IAV infection (Forero et al, 2015;Yang et al, 2022). Following IAV infection, two major cellular pathways are activated to initiate the antiviral innate immune response: Toll-like receptors (TLRs) and RIG-I-like receptors (RLRs) (Iwasaki and Pillai, 2014) (Figure 5).…”
Section: Iav Ns1 Inhibition Of Ifn Productionmentioning
confidence: 99%